Pengaruh Kompetensi, Independensi, Dan Etika Auditor Terhadap Kualitas Audit Aparat Inspektorat - Witta Widiya; Efrizal Syofyan (Universitas Negeri Padang, 2020)
The purpose of this study was to analyze the effect of competency, independence, and auditor ethics on audit quality in Inspectorate Office. Type of this research is a quantitative researh. The population in this study were auditors in inspectorate office West Sumatera province with 35 samples taken. The technique of sample collection is total sampling method. The sources of the data of this research is the primary data. The technique of the data collection is questionnaires. The data were analyzed using multiple regression analysis using SPSS version 25. Data analysis methods used in this study are multiple linier regression analysis, with audit quality as the dependent variabel, competency, independence and auditor ethics as the independent variabel. This result of the reseacrh support the third hypotheses, where the research shows that auditor ethics has an effect on audit quality of examiners at the inspectorate West Sumatera province. The results also show that competency and independence have no effect on audit quality of examiners at the inspecorate West Sumatera provinsi.